2004
DOI: 10.1111/j.1523-1755.2004.00717.x
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular expression of the ATP-sensitive P2X7 receptor in diabetic and hypertensive rat models

Abstract: We conclude that the P2X(7) receptor is not expressed appreciably under normal conditions, but that following glomerular injury it is significantly up-regulated, mainly in podocytes, though also in endothelial and mesangial cells, of animals with STZ-induced diabetes mellitus or TGR hypertension. Although the exact function and regulation of this receptor remain unclear, its association with inflammatory cytokine release and cell death suggests that increased expression might be involved in the pathogenesis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
103
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(106 citation statements)
references
References 51 publications
1
103
0
2
Order By: Relevance
“…The first expression of P2X 7 R in renal disease was described in a rat model of diabetes and hypertension [60]. Moreover, Solini and colleagues [61] demonstrated the importance of P2X 7 R activation in TGF-β1 secretion and ECM production from mesangial cells.…”
Section: Renal Fibrosismentioning
confidence: 98%
“…The first expression of P2X 7 R in renal disease was described in a rat model of diabetes and hypertension [60]. Moreover, Solini and colleagues [61] demonstrated the importance of P2X 7 R activation in TGF-β1 secretion and ECM production from mesangial cells.…”
Section: Renal Fibrosismentioning
confidence: 98%
“…The released ATP has mitogenic effects on glomerular epithelial cells, probably via P2Y 1 receptors, and ATP has the potential to contribute to remodelling of the kidney and progression to chronic renal failure, a condition that presents with sympathetic overactivity [391]. While P2X7 receptors are only weakly expressed in healthy glomerulus, following glomerular injury (for example, in diabetes and hypertension), it is significantly upregulated, mainly in podocytes, but also in endothelial and mesangial cells [393]. P2X7 receptors have been shown to participate in disturbed intracellular calcium homeostasis in peripheral blood mononuclear cells of patients with chronic kidney disease [205].…”
Section: Renal Injury and Failurementioning
confidence: 99%
“…There is an exaggerated response to adenosine in kidneys from high salt-fed rats [223]. While the P2X7 receptor is only weakly expressed in healthy kidney glomerulus, it is significantly upregulated in ren-2 transgenic hypertension [393]. In a recent paper, it was shown that P2X7 receptor antagonism prevented the development of salt-sensitive hypertension and renal injury in Dahl salt-sensitive rats [176].…”
Section: Hypertensionmentioning
confidence: 99%
See 1 more Smart Citation
“…Babelova et al showed that the secretion of the pro-inflammatory master cytokine interleukin (IL)-1β during inflammatory renal injury interacts with purinergic P2X4/P2X7 receptors [59]. Moreover, P2X7 receptor expression in glomeruli was augmented tenfold in diabetic and hypertensive rat models when compared to that of healthy rat glomeruli [60]. Purinergic signaling has also been related to renal protection via A 2a adenosine receptor activation in conditions of reperfusion injury [61].…”
Section: Bladder Dysfunction and Glomerular Injurymentioning
confidence: 99%